Biophysics of Cold Adaptation and Acclimatization. - Laursen,Gary A; Selby, George M (1979)
Contents: Projects and Productivity; Research Accomplishments; CETA Arctic Mammalogy Program; First International Symposium on Arctic Mycology; Animal Care and Maintenance; and Facility Staff Improvements and Administration.